Densidade mineral óssea nas fraturas do fêmur proximal - Bolze, Carlos Daniel de Garcia (2013)
Osteoporotic fractures always bring morbidity to patients and in the proximal femur, also mortality. International studies have sought to examine the relationship between bone mineral density and hip fractures; however, Brazil and Latin America still need more data. This study aims to describe the bone quality of patients who suffered fractures of the proximal femur treated at a hospital in southern Brazil and make a comparative analysis according to gender, BMI and the different types of fractures. Patients and Methods: We analyzed in a transversal study 118 patients with proximal femur fractures, 56 with femoral neck fractures and 62 with trochanteric fractures. Of these, 16 were male and 102 female. Femoral neck fractures were classified according to the classification of Garden and later divided into Stable (Garden I and II) and Unstable (Garden III and IV). The trochanteric fractures were classified according to AO-OTA and divided into Stable (31A1 up to 31A2.1) and Unstable (31A2.2 up to 31A3.3). Results: Fractures classified as Stable showed T-score values lower than those unstable for all measurement locations in the proximal femur. Statistical significance was detected in the difference between the measurements obtained in the trochanteric region and the spine (p = 0.042 and p = 0.024 respectively) when comparing unstable trochanteric and femoral neck factures. Trochanteric fractures tend to occur in patients above 80 years old while cervical fractures are more frequent above 70 years old. Patients with trochanteric fractures had lower BMI than those with fractures of the femoral neck (p = 0.022). Conclusion: The trochanteric fractures tend to occur in older patients and are associated with the BMI lower than those patients with femoral neck fractures. Unstable fractures have higher bone mineral loss in the trochanteric region, which may indicate greater loss in this region with advancing age, favoring the occurrence of trochanteric fractures.